2008
DOI: 10.1016/j.jacc.2008.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Statins Alone Versus Statins Plus Ezetimibe on Carotid Atherosclerosis in Type 2 Diabetes

Abstract: Objective This secondary analysis from the Stop Atherosclerosis in Native Diabetics Study examines the effects of lowering low-density lipoprotein cholesterol (LDL-C) with statins alone versus statins plus ezetimibe (E) on common carotid artery intimal medial thickness (CIMT) in patients with type 2 diabetes and no prior cardiovascular event. Background It is unknown whether the addition of E to statin therapy affects subclinical atherosclerosis. Methods Within an aggressive group (target LDL-C ≤70mg/dL; n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(78 citation statements)
references
References 16 publications
6
67
1
4
Order By: Relevance
“…Other therapies with complementary but differing mechanisms of action have the potential to benefit endothelial function. In T2D patients, aggressive LDLcholesterol lowering with statins alone or statins plus ezetimibe achieved a similar regression of CIMT in patients who had equivalent LDLcholesterol reductions [236], but comparative therapeutic effects on endothelial function were not studied. Omega-3 fatty acid supplementation has been shown to improve endothelial function in T2D [153,[156][157][158][159], including postprandial endothelial function [156][157][158].…”
Section: Combination Therapiesmentioning
confidence: 99%
“…Other therapies with complementary but differing mechanisms of action have the potential to benefit endothelial function. In T2D patients, aggressive LDLcholesterol lowering with statins alone or statins plus ezetimibe achieved a similar regression of CIMT in patients who had equivalent LDLcholesterol reductions [236], but comparative therapeutic effects on endothelial function were not studied. Omega-3 fatty acid supplementation has been shown to improve endothelial function in T2D [153,[156][157][158][159], including postprandial endothelial function [156][157][158].…”
Section: Combination Therapiesmentioning
confidence: 99%
“…In T2D patients, combination ezetimibe with lower-dose statin therapy achieved LDL-cholesterol and non-HDLcholesterol targets more effectively than statin alone [98]. In the Stop Atherosclerosis in Native Diabetes Study (SANDS), lowering of LDLcholesterol to aggressive targets with ezetimibe plus statin, or statin alone, achieved regression of carotid intima-media thickness (CIMT), a surrogate marker of atherosclerosis, in T2D patients [99]. This related to the reduction in LDLcholesterol and not the minimal changes in triglycerides or HDL-cholesterol [99].…”
Section: Addressing Residual Cardiovascular Risk With Combination Phamentioning
confidence: 99%
“…In the Stop Atherosclerosis in Native Diabetes Study (SANDS), lowering of LDLcholesterol to aggressive targets with ezetimibe plus statin, or statin alone, achieved regression of carotid intima-media thickness (CIMT), a surrogate marker of atherosclerosis, in T2D patients [99]. This related to the reduction in LDLcholesterol and not the minimal changes in triglycerides or HDL-cholesterol [99]. Hence, further evidence is required to support the role of ezetimibe in treating residual CVD risk in statintreated T2D patients.…”
Section: Addressing Residual Cardiovascular Risk With Combination Phamentioning
confidence: 99%
“…8 In a recent randomized study, Tsujita et al demonstrated the superiority of the combination of ezetimibe and statin on coronary atherosclerosis, compared with statin alone, in patients with coronary artery disease. 9 Similarly, the SANDS clinical trial concluded that the beneficial effects of the combination of ezetimibe plus statin on carotid atherosclerosis was similar to that of statin alone in patients with similar reduction in LDL-C. 10 Other clinical trials on the combination of ezetimibe and statin on carotid atherosclerosis, however, noted variable results: both beneficial 10 and non-favorable outcomes. 11,12 Thus, the anti-atherosclerotic effects of ezetimibe remain controversial.…”
Section: Calculation Of Endpointsmentioning
confidence: 99%